Blockbuster Marxism. (March 2015) - Agger, Ben; Luke, Timothy W.
Thomas Piketty's critique of capitalism, Capital in the 21st Century (2014), is examined in light of earlier Marxist and neo-Marxist analyses. It is noted that Piketty's important main finding, that inequality has increased under capitalism, is not matched by his solution, the 'social state', which hinges on a tax on capital and is not a fundamental rethinking of capitalism. Alternative analyses of a global 'flash capitalism' are explored.